Levinsenia species (Annelida: Polychaeta: Paraonidae) from the Sea of Marmara with descriptions of two new species - Erdoğan-Dereli, Deniz; Çinar, Melih Ertan (Zootaxa, 2021)
The present study deals with the diversity of the genus Levinsenia in the Sea of Marmara. The specimens of Levinsenia were collected on soft and hard substrata at depths ranging from 10 to 500 m at 98 stations in 2013. Among the material, two new species, namely Levinsenia longobranchiata n. sp. and L. vulgaris n. sp., and five already known species (L. demiri, L. kosswigi, L. materi, L. marmarensis, L. tribranchiata) were found. Levinsenia longobranchiata n. sp. is mainly characterized by having very long branchiae (longer than the body width) and five prebranchial chaetigers without notopodial postchaetal lobes. Levinsenia vulgaris n. sp. is mainly characterized by having short branchiae (shorter than the body width) and five prebranchial chaetigers with notopodial postchaetal lobes. The SEM images enabled us to define some previously neglected/indistinct characters in the taxonomy of Levinsenia such as the degree of the fusion of the branchiae with the notopodia; the morphology of dorso-lateral irregular pores, cheek organ, ciliated patches and lateral organs on the lateral sides of the prostomium; and the shape and distribution of the lateral sense organs along the body. All species found in the region were presented and described, by also taking these novel characters into account.